Strengthening Practice Methods In The Implementation Of Japanese Language Course Learning At The Zai Japan Course And Training Institute (LKP) - Ganiadi, Mochamad; Silvi Amelia; Inayah, Iin; Sihaloho, Rosana Bernarda; Widiyanti, Dewi; Baehaki (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Japanese language education in Indonesia, particularly in industrial areas such as Cilegon and Serang, is increasingly in demand as the need for a workforce with proficiency in Japanese grows. Zai Japan Training and Course Center (LKP) in Serang plays a vital role in preparing students to be ready for employment in Japanese companies. To enhance the effectiveness of learning, LKP Zai Japan applies a practice-based method that includes daily reporting in Japanese, the use of Japanese in dormitory life, work practice, and communication simulations in various real-life situations. This study aims to analyze the implementation of the practice-based method in Japanese language learning and its impact on students' language competencies. A qualitative approach with observation and interviews was used to collect data. Observations were made directly in the classroom learning process and social interactions among students, while semi-structured interviews were conducted with the managers and teachers of LKP Zai Japan. The results show that the practice-based method significantly contributes to improving students' speaking, listening, reading, and writing skills. The use of Japanese in daily life accelerates students' language competency development. However, there are challenges such as limited facilities, the lack of qualified Japanese language instructors, and varying levels of student motivation. This study offers recommendations for LKP Zai Japan managers in designing a curriculum that better aligns with industry needs and improving the effectiveness of practice-based learning, in order to create a more competent workforce ready to meet the demands of the job market.